1985
DOI: 10.1111/j.1439-0264.1985.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Paranasal Sinuses of the One Humped Camel (Camelus dromedarius)

Abstract: A gross anatomic and radiological examination of the paranasal sinuses of the camel is described. Radiological examination was enhanced through the use of a barium sulphate paste.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…However, Moustafa and Kamel () in camel reported the excavation of the frontal sinus extends beyond the angle of divergence of the external parietal crest. In agreement with Ahmed et al () in camel and Kumar and Dhingra () and Alsafy et al () in buffalo, the present study found a short curved supraorbital canal, which passes through the caudal frontal sinus.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, Moustafa and Kamel () in camel reported the excavation of the frontal sinus extends beyond the angle of divergence of the external parietal crest. In agreement with Ahmed et al () in camel and Kumar and Dhingra () and Alsafy et al () in buffalo, the present study found a short curved supraorbital canal, which passes through the caudal frontal sinus.…”
Section: Discussionsupporting
confidence: 93%
“…Cattle and buffalo also have a nuchal and cornual diverticulum that extends into the frontal sinus (Alsafy et al, ; Budras et al, ; Nickel et al, ). The frontal sinus boundaries are limited to the frontal bone and Ahmed et al () have reported similar observations in camel. However, Moustafa and Kamel () in camel reported the excavation of the frontal sinus extends beyond the angle of divergence of the external parietal crest.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations